If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3y + -1z = 11 Solving 2x + 3y + -1z = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 2x + 3y + -3y + -1z = 11 + -3y Combine like terms: 3y + -3y = 0 2x + 0 + -1z = 11 + -3y 2x + -1z = 11 + -3y Add 'z' to each side of the equation. 2x + -1z + z = 11 + -3y + z Combine like terms: -1z + z = 0 2x + 0 = 11 + -3y + z 2x = 11 + -3y + z Divide each side by '2'. x = 5.5 + -1.5y + 0.5z Simplifying x = 5.5 + -1.5y + 0.5z
| x+3y+6z=15 | | 50000000000=1 | | 2x+4y+z=15 | | 35*3-x=235 | | 4x-12y=9 | | 1579+x=820 | | 4x-12y+9= | | sqrt(-9x+7)-2=4x | | 16x^2+25x-3=0 | | 1579-x=820 | | x+1579=820 | | (3m+4)(m^2-3m+5)=y | | x-1.579=820 | | 6x+(-5)=25 | | 6x+8=(16x-4) | | 6x+8=2(16x-4) | | 4x(6-x)(4-x)=0 | | 7x^2+42x= | | -12+5+-6+12+-5= | | 16x-4=(6x+8) | | 16x-4=2(6x+8) | | 17+-28+56+28+-17= | | -8+8+5+9+-5+6+-9= | | 3-3(lnx)=4 | | 6+-9+8+9+-6+3= | | -y^2-9y-54=0 | | 594=(x+2)6x | | 37+4+-37+-5= | | 3+-8+-3+8= | | 9x+5=2*(5x-4) | | 35/50 | | 9x+5=2*5x-4 |